Irregular menses predicts ovarian cancer: Prospective evidence from the Child Health and Development Studies. Issue 5 (29th April 2016) - Cirillo, Piera M.; Wang, Erica T.; Cedars, Marcelle I.; Chen, Lee‐may; Cohn, Barbara A.
Abstract : We tested the hypothesis that irregular menstruation predicts lower risk for ovarian cancer, possibly due to less frequent ovulation. We conducted a 50‐year prospective study of 15, 528 mothers in the Child Health and Development Studies cohort recruited from the Kaiser Foundation Health Plan from 1959 to 1966. Irregular menstruation was classified via medical record and self‐report at age 26. We identified 116 cases and 84 deaths due to ovarian cancer through 2011 via linkage to the California Cancer Registry and Vital Statistics. Contrary to expectation, women with irregular menstrual cycles had a higher risk of ovarian cancer incidence and mortality over the 50‐year follow‐up. Associations increased with age ( p <0.05). We observed a 2‐fold increased incidence and mortality by age 70 (95% confidence interval [CI] = 1.1, 3.4) rising to a 3‐fold increase by age 77 (95% CI = 1.5, 6.7 for incidence; 95% CI = 1.4, 5.9 for mortality). We also found a 3‐fold higher risk of mortality for high‐grade serous tumors (95% CI = 1.3, 7.6) that did not vary by age. This is the first prospective study to show an association between irregular menstruation and ovarian cancer—we unexpectedly found higher risk for women with irregular cycles. These women are easy to identify and many may have polycystic ovarian syndrome. Classifying high‐risk phenotypes such as irregular menstruation creates opportunities to find novel early biomarkers, refine clinical screening protocols and potentially develop new risk reduction strategies. These efforts can lead to earlier detection and better survival for ovarian cancer. Abstract : What's new? The lack of specific early symptoms in ovarian cancer, aggressiveness of some of the histopathologic subtypes and need for more effective screening and treatment strategies are evidenced by a dismal 5‐year survival rate for all stages. While several studies have reported ovarian cancer associations with menstrual cycle variability, the findings are inconsistent. This study provides the first prospective evidence that women with irregular menstrual cycles are at higher risk of ovarian cancer. Discovering high‐risk phenotypes such as irregular menstruation creates opportunities to find novel early biomarkers, refine clinical screening protocols and potentially develop new risk reduction strategies for ovarian cancer.